The Influence of Job Satisfaction and Job Stress on the Desire to Resign Voluntarily - Fairudeen, Mohamed; Tajuddin, Dewi; Monil, Muzalifah (Journal of Human Capital Development (JHCD), 2021)
ABSTRACT The aim of this study is to determine factor affecting job stress, job satisfaction, work engagement, and organisational commitment influence municipal council employees’ desire to resign. A total of 209 valid responses collected. Hypotheses were tested through correlation and regression analytic procedures to predict and estimate the relationships between the variables. The findings showed that three out of four of the independent variables (job stress, job satisfaction and organisation commitment) had significant impact on the employees’ desire to resign. Some key conclusions emerged from the regression analysis. Firstly, there was important relationship between job stress, job satisfaction and employees’ desire to resign. Secondly, employees’ desire to resign could be related to organisational commitment. This indicates that high of job satisfaction do not reduce people’s desire to leave their jobs, but lower organisational commitment has direct impact towards employees’ desire to resign. Keywords: Job Satisfaction, Job Stress, Work Engagement, Desire to Resign